Contemporary comprehension of root canal biofilms and future perspectives: Part 2 - Vijetha Vishwanath; Prasanna Neelakantan (Wolters Kluwer Medknow Publications, 2024)
In Part 1 of this commissioned review, we discussed the basic biology of biofilms, its assembly, biogeography, and physicomechanical properties. In the second part of this review, we critically discuss the literature pertaining to microbiology of endodontic diseases, types of root canal infections, microbial dynamics, and host evasion strategies and highlight the concept of functional redundancy. Then, we review the role of fungi in endodontic diseases and provide an important narrative on the role of biofilms in weakening dentin. Finally, we briefly review the goals of prevention and treatment of apical periodontitis and provide futuristic perspectives to reinforce critical points that will aid future research and discovery.